Effects of Septin-14 Gene Deletion on Adult Cognitive/Emotional Behavior - Chen, Kuan-Ru; Wang, Han-Yu; Liao, Yi-Han; Sun, Li-Han; Huang, Yu-Han; Yu, Lung; Kuo, Pao-Lin (Frontiers in Molecular Neuroscience, 2022)
While various septin GTPases have been reported for their physiological functions, their roles in orchestrating complex cognitive/emotional functions in adult mammals remained scarcely explored. Two sexes of 12-week-old septin 14 (SEPT14) knockout (KO) and wildtype (WT) mice were subjected to a comprehensive behavioral test battery. Sexually dimorphic effects of brain SEPT14 KO were noticed on inhibitory avoidance (IA) and hippocampal mGluR5 expression with greater IA latency and elevated mGluR5 level exclusively in male KO mice. Moreover, SEPT14 KO appeared to associate with stress-provoked anxiety increment in a stress-related navigation task regardless of animals’ sexes. While male and female WT mice demonstrated comparable cell proliferation in dorsal and ventral hippocampal dentate gyrus (DG), two sexes of SEPT14 KO mice had heightened cell proliferation in ventral DG. Finally, male and female SEPT14 KO mice displayed dampened observational fear conditioning magnitude and learning-provoked corticosterone secretion as compared to their same-sex WT mice. These results, taken together, prompt us to conclude that male, but not female, mice lacking of septin 14 gene may exhibit increases in aversive emotion-related learning and dorsal/ventral hippocampal mGluR5 expressions. Moreover, deletion of SEPT14 may associate with elevated ventral hippocampal DG cell proliferation and stress-provoked anxiety-like behavior, while dampened vicarious fear conditioning magnitudes.